PERAN BADAN MUSYAWARAH NAGARI SUNGAI SARIAK SEBAGAI PENGAWAS PENGGUNAAN ANGGARAN YANG BERSUMBER DARI DANA DESA - Titra Junaidi (LPPM Universitas Ekasakti Padang, 2019)
The Role of the Nagari Consultative Body is a form of democracy at the nagari level, Bamus functions to determine the nagari regulations together with the nagari government, to accommodate and channel the aspirations of the nagari community and to oversee the nagari financial management. Regional District of Padang Pariaman Number 05 of 2009 the role of Bamus has not been maximized in accommodating the aspirations of the community, the lack of socialization about development planning and supervision of the Nagari Government and BAMUS coordination in the meeting agenda is expected to play a more effective role in the future management of the nagari financial management. Based on the background description that has been conveyed How is the Role of Bamus in supervising the implementation of the Nagari Government in Nagari Sungai Sariak Kecamatn VII koto Sungai Sariak and What are the obstacles faced by Bamus in supervising the Nagari Government and the efforts made in Nagari Sungai Sariak District VII Koto Sariak. River The research method used is descriptive analytical method. Descriptive research analyzes and presents data and facts systematically so that they can be more easily understood and concluded. This study aims to determine how the role of the Nagari Consultative Body as a Supervisor of the Use of Budgets sourced from Village Funds, especially in the Sariari Nagari Sungai VII, Koto Sungai Sariak District. The results of the research in Nagari, have concluded that the Nagari Consultative Body has not worked optimally in accordance with the role of BAMUS in the Regional Regulation of Padang Pariaman District Number 05 of 2009. The Nagari Musaraharah Agency (Bamus) in carrying out the Nagari fund supervision function has not been maximized, this has occurred. because the Nagari Deliberation Board (Bamus) in carrying out its duties Bamus experienced several obstacles The Sariak River Nagari Deliberation Board (Bamus) was expected to be able to carry out its supervisory function and Bamus's role in the Nagari deliberation to the maximum and be able to communicate well as a partner of the ngari government.